Study on Concrete Pier Impact Performance after Implementing Equal Cross-Section Stainless Steel with Protection from Closed-Cell Aluminum Foam - Xiwu Zhou; Honglong Zhang; Wenchao Zhang; Guoxue Zhang (Shock and Vibration)
In the present study, in order to examine the impact performances of ordinary reinforced concrete bridge piers which have been replaced by stainless-steel bars of equal cross-sections under the protective condition of anticollision material, the impact dynamic responses of the ordinary reinforced concrete bridge piers, with replacements under the protection of closed-cell aluminum foam, were compared and analyzed using an ultrahigh drop hammer impact test system. The results showed that when the impact velocity was small (for example, less than 1.42 M/s), after the implementation of equal cross-sectional replacements, the closed-cell aluminum foam had been in an elastic or yield stage. During that stage, the impact forces of the stainless-steel reinforced concrete piers were larger than those of the ordinary reinforced concrete piers, and the relative ratios were stable at approximately 28 to 34%. In addition, the relative ratios of the displacements at the tops of the components were also found to be stable at approximately 22%, and the change rates of the concrete ultrasonic damages were approximately the same. However, when the impact forces had increased (for example, more than 1.67 m/s), the closed-cell aluminum foam entered a densification stage, and the peak impact force ratios decreased sharply. It was also observed that the relative peak displacement ratios at the tops of the components displayed increasing trends, and the change rates of the concrete ultrasonic damages had displayed major flux. Therefore, the replacement of the ordinary piers with stainless-steel bars had increased the possibility of shear failures.